2014
DOI: 10.1002/bjs.9438
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of hepatoduodenal ligament lymph nodes in resectional surgery for gastric cancer

Abstract: It is inappropriate to include the HDLN in the distant metastatic lymph node group in gastric cancer. The seventh AJCC criteria for node grouping should be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Lee et al [14] reported that prognosis differed between patients with hepatoduodenal (No.12) LN metastasis and those with distant metastases. Similarly, in this study, survival outcomes were similar between cases of No.12a LN metastasis and those of LN involvement in the AJCC (7 th edition)-defined D2 lymphadenectomy region, although survival was poorer in cases of No.12a LN metastasis than in those of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [14] reported that prognosis differed between patients with hepatoduodenal (No.12) LN metastasis and those with distant metastases. Similarly, in this study, survival outcomes were similar between cases of No.12a LN metastasis and those of LN involvement in the AJCC (7 th edition)-defined D2 lymphadenectomy region, although survival was poorer in cases of No.12a LN metastasis than in those of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies calculated the incidence of lymph node metastases in second level nodes, removed by D2 dissection. The rates of nodal metastasis in second-level nodes (8a, 10, 11p/d, 12a) range according to depth of invasion, histotype, tumor location and other pathological factors (9,(20)(21)(22)(23). It is evident that removing these metastatic nodes could favour an increase in surgical radicality.…”
Section: Removal Of Potentially Metastatic Nodes and Increase In Surgmentioning
confidence: 99%
“…Analyzing the data of 1872 patients, LN involvement in station no.12 was 3.6% whereas HDLN metastasis was not a significant factor for survival in multivariate analysis and the 5year survival rate of 41 patients with HDLN metastasis without distant metastasis at any other site was significantly higher than that among 120 patients with stage Ⅳ disease without HDLN metastasis. It is suggested that the inclusion of HDLN in the distant metastatic LN group in gastric cancer is inappropriate and that the seventh American Joint Committee on Cancer criteria for node grouping should be revised [56] . The incidence of no.…”
Section: Middle and Distal Gastric Cancermentioning
confidence: 99%